Optimalisasi Perangkat Evaluasi Pembelajaran Pada Penilaian Akhir Semester Dengan Program Ms. Excel Di SMKN 4 Klaten Tahun 2016 - Setomo, Anasanti Darah; , Prof. Dr. Sutama, M.Pd; , Dr. Sumardi, M.Si (2017)
This research aims to develop evaluation tools, test the feasibility and effectiveness of the design learning tools on the semester's final assessment using Ms. Excell program. Stages of research began with the development which consists of literature studies, field studies and proceed with product development. The next stage is validation by the Forum Group Discussion Team, consisting of academics, practitioners, policy makers and representatives of teachers, followed by validation Judgement Expert and limited field trial. The last step is to test the main field. Results from the literature, obtained a theory about the evaluation of learning and theory of Excell, data from field studies percentage of constituent devices overall evaluation of 51%, consisting of the preparation of the device about 79%, the preparation of the analysis of student scores 71%, and the preparation of quality analysis about 3 %. Based on the literature study and field, developed products Application Preparation of Evaluation of Learning (Apep) with Excell. Tim FGD and experts providing recommendations and revised in some parts, but in general, Apep acceptable. Limited field trial results, an increase in the overall effectiveness of the limited field trial increased from 52% to 96%. Average main results of field trials, an increase of 52% to 98%. T test results, thit< tcritical (-34.03767209< 1.699126996). It was concluded that the hypothesis is accepted, or the design of learning evaluation device with Ms. Excell program effectively optimize the preparation of the learning evaluation on the semester's final assessment Keyword: Application; learning evaluation; evaluation tool